Endocan Levels and Endothelial Dysfunction in Patients With Sarcoidosis. (November 2018) - Aciksari, Gonul; Kavas, Murat; Atici, Adem; Kul, Seref; Erman, Hayriye; Yilmaz, Yusuf; Demircioglu, Kenan; Yalcinkaya, Emre; Kanbay, Asiye; Caliskan, Mustafa
A systemic inflammatory reaction is a common feature of both sarcoidosis and atherosclerosis. Endothelial-cell specific molecule 1 (endocan) is a marker of vascular pathology which also shows a correlation with inflammation, endothelial dysfunction, and atherosclerosis. The objective of this study was to evaluate the vascular involvement in sarcoidosis using serum endocan levels and brachial artery flow–mediated dilation (FMD), a marker of endothelial dysfunction. We included 53 patients with sarcoidosis without conventional cardiovascular risk factors and 40 healthy controls. Endothelial function was assessed using FMD. Endocan concentrations were measured using a commercially available enzyme-linked immunoassay. Patients with sarcoidosis had significantly higher endocan levels (306 [68] ng/mL vs 269 [73] ng/mL; P = .039) and lower FMD (2.7% [2.3%-3.2%] vs 8% [5%-13%]; P < .001) compared with the healthy group. A negative correlation was found between endocan levels and FMD in the sarcoidosis group ( r = −.325, P < .007). We conclude that sarcoidosis is associated with high levels of endocan and lower FMD values, which may indicate endothelial dysfunction and an early stage of atherosclerosis.